Dental Age Assessment of United States Black and White Children: Performance Reliability of Harris and McKee (1990). (22nd March 2023) - Collier, Shanetha L.; Lewis, James M.; Kasper, Kathleen A.; Marks, Murray K.; Heidel, R. Eric
Abstract: Medicolegal authorities use forensic dental age assessment of children to establish a biologic profile to assist in human identification, answer questions related to immigration, and answer questions used to substantiate eligibility for social benefits. The goal of this study was to assess the performance reliability of the child dental age assessment data previously published for White and Black children in the United States. A total of 432 dental panoramic radiographs were obtained from 3 geographic locations in the United States: Memphis, Tennessee, Knoxville, Tennessee, and Saint Louis, Missouri. Radiographs were staged, and the estimated age was calculated using the previously published data. Multiple age assessments were conducted to determine the effect of excluding certain teeth on estimated age. The results indicated estimated ages using the previously published reference data set were accurate and concordant with known chronologic age across the ancestral, sex, and geographic categories. The results also indicated that the known chronologic age fell within one standard deviation of the estimated age more than the statistical expectation for most categories. Excluding canines provided the most accurate estimation of known chronologic age.